Analysis Of The Influence Of Growth Opportunities, Company Size And Financial Difficulties Risk On Accounting Conservatism Of Potentially Bankrupt Manufacturing Companies In Indonesia - Titin Hartini; Loso Judijanto; Umi Setyorini; Alfiana; Mahdi (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2023)
The purpose of this study is to ascertain whether accounting conservatism is influenced by firm size, prospective financial issues, and corporate growth opportunities, and whether this influence is mitigated by leverage. The author of this study employed the quantitative causal method. Purposive sampling is the procedure used in the sampling approach. The author used secondary data for this study. The yearly financial reports of manufacturing companies registered on the Indonesian Stock Exchange (BEI) provided the author with the secondary data used in this study. The author accessed the websites of each organization that satisfied the sample requirements in addition to the IDX website, which can be found at www.idx.co.id, to gather the necessary data. Using moderate regression analysis, the hypothesis test in this study examines the impact of the independent variable on the dependent variable and its moderating variable. The following conclusions can be made from this research based on the experiments that were conducted: Accounting conservatism is unaffected by a company's size. Accounting conservatism remains unaffected by potential financial difficulties. Accounting conservatism is influenced by growth potential. The relationship between accounting conservatism and corporate scale cannot be mediated by leverage. The association between the possibility of financial issues and accounting conservatism cannot be mitigated by leverage. The link between development prospects and accounting conservatism can be tempered by leverage.